Peran Kepala Sekolah Sebagai Supervisor dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam Sekolah Dasar - Nilda Nilda; Hifza Hifza; Ubabuddin Ubabuddin (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The method used in this research is descriptive qualitative analysis. The descriptive method is intended that the researcher explains the real conditions of supervision carried out by the principal at SDS Sulthoniyah sambas, while qualitative analysis is used when examining the role of the supervisor (supervisor) of the principal in improving the performance of PAI teachers at SDS Sulthoniyah sambas. The scope of this research is field research by taking the location at SDS Sulthoniyah Sambas. Data collection techniques using interviews, documentation, and observation. Data sources consist of primary data and secondary data. In conducting research naturally the researcher himself acts as a research instrument. The data analysis technique used by the researcher is data analysis, data reduction, data categorization, data interpretation and conclusions. The results of this study are that the implementation of supervisory duties includes the elements; personal, material, and operational. The steps taken by the supervisor in the supervision, namely; (1) planning and preparation designed through supervisory work shop meetings at the beginning of the year which are then broken down into semester and monthly plans, (2) implementation through collective coaching and school monitoring, and (3) assessment through instruments which has been prepared. Teacher performance at SDS Sulthoniyah Sambas has shown good performance standards, this is indicated by their ability to manage learning well. The indicator is that PAI teachers at SDS Sulthoniyah Sambas have carried out the following teacher duties: (1) developing lesson plans properly, (2) implementing learning, (3) assessing student learning achievement according to procedures, and (4) implementing follow-up on the results of the assessment through remedial and enrichment.